Paediatric out-of-theatre procedural sedation at a tertiary children's hospital: A prospective observational study - Lapere, Cherese (Department of Anaesthesia and Perioperative Medicine, 2022)
Background: This tertiary referral centre is one the largest paediatric hospitals in Africa. Despite an increasing number of surgical and diagnostic procedures being performed annually, a formal out-of-theatre sedation service does not exist. Procedural sedation and analgesia (PSA) is an important adjunct in behavioural management for invasive procedures in children. Objective: A prospective, observational study was performed at RCWMCH, aimed primarily at defining the number of cases of PSA performed outside the operating theatre. Methods: Data was collected from all procedural out-of-theatre sedations performed over a period of three months, including ward patients and out-patient departments. All children < 13 years of age were included. Results: A total of 639 sedations were performed. Of these sedations, 288 (45.0%) paper responses were captured and analysed. The reported incidence of desaturation was 4.2% (12/288), laryngospasm 0.3% (1/288) and nausea and vomiting 2.4% (6/288). Three cases required conversion to general anaesthetic, and three cases were abandoned due to inadequate sedation. In 16.3% (47/288) of cases the clinician was an operator sedationist (the same person performing the sedation and the procedure). In 90.6% of cases the intravenous route was utilized, with dexmedetomidine, ketamine and propofol being the three most commonly used agents. Conclusion: 639 PSA events were recorded in 3 months. The 288 events analysed were safely performed with minimal serious reported events. These results compare favourably with international studies and provide quantitative evidence as a prelude to setting up a dedicated sedation service at our facility.